BT-06 CENTRAL NERVOUS SYSTEM HEMANGIOBLASTOMA; DIFFERENCES IN CLINICAL PICTURE OF SPORADIC CASES AND VON-HIPPEL LINDAU DISEASE IN 184 CASES. (16th December 2019) - Takami, Hirokazu; Burns, Terry; Parney, Ian
Abstract: INTRODUCTION: Central nervous system hemangioblastoma (CNS HGB) is a rare neoplasm, which predominantly arise in the posterior fossa and spinal cord. The etiology is divided into sporadic and von-Hippel Lindau (VHL) disease. The difference in clinical picture of these 2 types of HGB and differentiation of treatment have not been extensively unraveled yet. METHODS: Retrospective analysis of consecutive, neurosurgically managed CNS HGB at Mayo Clinic, 1988–2018. RESULTS: 117 sporadic and 67 VHL HGBs were treated by Mayo Clinic. No significant difference in sex was observed. Compared with sporadic cases, VHL cases were younger (51.8 vs 36.0 years old, p<0.0001), had more frequent family history (0.0 vs 41.5 %, p<0.0001), and higher frequency of germline alteration (0.0 vs 84.2 %, p<0.0001). Regarding imaging findings, VHL cases had multiple lesions at presentation more frequently (3.4 vs 82.1 %, p<0.0001), it was more common for sporadic lesions to contain cysts (72.2 vs 51.0 %, p=0.0004), the solid portion rate in the entire lesion was larger in VHL lesions (60.2 vs 69.5 %, p=0.02), and the volume was larger in sporadic cases (15.1 vs 6.6 cc, p<0.0001). Regarding treatment, 131 and 123 surgeries were performed for sporadic and VHL cases, respectively, among which the indication of surgery was preventative in 8.4 and 47.3 %, respectively (p<0.0001). VHL cases had higher number of treatments per case in the follow-up (1.3 vs 2.1, p<0.0001). Recurrence-free survival of sporadic cases was significantly longer than that of VHL cases (p=0.007) and overall survival was longer in sporadic cases than VHL, but not significant (p=0.07). CONCLUSION: Clinical presentation and tumor appearance on imaging are highly dependent on the etiology. Differences in clinical manifestations require further study, but may reflect contrasting tumor biology that are tied to genetic differences.